Women's reasons and perceptions around planning a homebirth with a registered midwife in Western Australia. Issue 1 (February 2020) - Hauck, Yvonne; Nathan, Elizabeth; Ball, Colleen; Hutchinson, Maureen; Somerville, Susanne; Hornbuckle, Janet; Doherty, Dorota
Abstract: Background: Qualitative evidence has provided rich descriptions around reasons for planning a homebirth with a midwife. Reasons and the importance, confidence and support around this option have not been examined by parity with a larger cohort. Aim: Examine women's characteristics, reasons and perceptions of the importance, confidence and support around choosing homebirth based upon parity. Methods: A mixed method approach was undertaken within a prospective cohort study in Western Australia where women planning a homebirth have the option of a publicly funded model or care from privately practising midwives. At recruitment a questionnaire collected demographic data, perceived importance, confidence and support plus reasons for choosing homebirth. A qualitative component included an open ended question that encouraged sharing of opinions providing textual data explored by content analysis. Findings: Reasons noted by 211 pregnant women for choosing homebirth were: avoidance of unnecessary intervention (58.8%), comfort and familiarity of home (34.1%), freedom of making own choices (25.6%), and having more continuity of care (24.2%). Reasons for planning homebirth were similar by parity, except for comfort of home being more important (44.0% vs 28.7%, p = 0.025) and continuity of care (13.3% vs 30.1%, p = 0.006) being less important to primigravid women. Themes revealed common beliefs around childbirth, appreciation for access to homebirth and a desire for greater awareness and less negativity around homebirth. Conclusion: Regardless of parity, homebirth was believed to be safe and supported by partners. Reasons identified from qualitative research to avoid intervention, the comfort of home, choice and continuity of care were supported.